Simplified phase-recovery method in temporal speckle pattern interferometry - Etchepareborda, Pablo Gonzalo (2014)
A simplified method for object phase recovering is implemented in temporal speckle pattern interferometry when the employed interferometer admits the introduction of a temporal carrier, and the well-known two-beam interferometry equation is verified. The spatiotemporal evolution of the object phase is isolated by modulating the acquired interferometric intensity signals with a known temporal carrier in order to carry out its analysis by using a bivariate empirical mode decomposition framework that avoids the application of the Hilbert transform, which is not suitable for intensity signals with abrupt fluctuations. The advantages and limitations of this technique are analyzed and discussed by comparing computation time and phase recovery capability with well-known phase-retrieval methods by means of numerical simulations and experimental data.